The first-in-Africa ex vivo drug sensitivity testing platform identifies novel drug combinations for South African leukaemia patient cohort - V. L. Kenmogne; M. M. Takundwa; E. E. Nweke; B. Monchusi; P. Dube; H. Maher; J. Du Toit; V. Philip-Cherian; P. N. Fru; D. B. Thimiri Govinda Raj (Scientific Reports)
Abstract In South Africa, leukemia remains a major health concern, posing significant challenges in treatment due to its varied subtypes. There is an unmet need for a testing pipeline that can identify drug effects on patient samples in an ex-vivo setting. Using the pilot study with South African patient samples, this paper reports the development of a drug-sensitivity testing pipeline for studying the drug effects in leukemia patient-derived cells. Forty-one (41) patients with Acute myeloid leukemia (AML) (n = 7), Chronic myelogenous leukemia (CML) (n = 30), and Chronic lymphocytic leukemia (CLL) (n = 4) were recruited for this study. Thirty (30) FDA-approved drugs were utilized for single drug sensitivity screening (DSS) on leukemia patient-derived cells with drug concentrations (1–1000 nM). The single DSS showed a distinct sensitivity pattern with different profiles among patients of the same subtype, confirming the need for precision therapy. This study observed irinotecan, used in solid tumour treatment, demonstrated efficacy in PBMCs in many patient samples compared to conventional leukemia drugs such as nilotinib. For drug combination studies, ten clinically relevant drugs were selected and tested based on the results of single drug sensitivity tests. This pilot study marks a crucial stride towards revolutionizing leukemia treatment in South Africa through an innovative ex vivo drug sensitivity testing platform. This pioneering initiative forms the basis for tailored and effective treatment options holding promise for more personalized treatment. Further exploration and validation of these findings could significantly contribute to cancer precision medicine efforts in South Africa.